Examining the Influence of Organizational Culture on Change Management: A Qualitative Inquiry - Mia Christy Patricia; A Sigit Pramono Hadi; Cahyatih Kumandang (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
This qualitative study investigates the intricate relationship between organizational culture and change management processes. Employing a qualitative approach, the research delves into the depths of organizational dynamics to comprehend how cultural factors shape and influence the implementation of change initiatives. Through in-depth interviews and thematic analysis, the study elucidates the multifaceted dimensions of organizational culture, exploring its manifestations, norms, and values. Findings reveal the pivotal role of organizational culture in facilitating or impeding change efforts, highlighting the significance of cultural alignment for successful change implementation. Moreover, the research underscores the importance of understanding cultural nuances and fostering a culture of adaptability and openness to navigate the complexities of change. The insights gleaned from this study offer valuable implications for practitioners and scholars engaged in change management endeavors, emphasizing the necessity of integrating cultural considerations into change strategies for enhanced organizational effectiveness and resilience.